INTERFERENCE IN THE SHORT TEXT OF BESAKIH TEMPLE - Martha Puspita, Ni Made Kajeng (Lingual Journal of Language and Culture; Vol 1 No 1 (2016)DO - 10.24843/LJLC.2016.v01.i01.p08, 2016)
The aim of this study is to analyze the four types of interferences; syntax, semantics, copula, and redundant found in “Besakih Temple” short text. The data were collected through library research with the necessary note-taking and documentation. The method used in analyzing this study is qualitative method. The result showed that interferences found in the text are covering linguistic aspects. It is furthermore called the negative transfer due to the result of contact with another language. The most common source of errors is lack of knowledge of the speaker about the language being used.
Keywords: interference, copula, redundant